Genetic signatures of bufadienolide resistance are poor predictors of cane toad toxin resistance in crocodilians - Alexandra K. Ross; Pierre Ibri; Jonathan K. Webb; Tim S. Jessop; Tim Dempster; Charlotte H. Mills; Tahneal Hawke; Mike Letnic; Stephen Frankenberg (Evolutionary Ecology, 2026)

Evolution of Paleogene to Early Miocene deep-water provenance sources in Sabah, northern Borneo reveals changing Proto-South China Sea paleogeography - H. Tim Breitfeld; Marco W.A. van Hattum; Robert Hall; Stuart Burley; Juliane Hennig-Breitfeld; Max Franzel; Simon M. Suggate; Pieter Vermeesch; Max Webb (Tectonophysics, 2026)

AIS data underrepresents vessel traffic around coastal Scotland - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Lauren Hartny-Mills; Alison Lomax; Rebecca Dudley; Pippa Garrard; Jenny Hampson; Sadie Gorvett; Hannah Lightley; et al. (Marine Policy, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Imperfect adaptation by freshwater crocodiles to the invasion of a toxic prey species - Mike Letnic; Tim Dempster; Tim S. Jessop; Jonathan K. Webb (Biological Invasions, 2024)
Novel interactions between invaders and native species that have evolved in their absence may impose strong selective pressures that drive species to extinction or prompt rapid co-evolution and learning. Here, we report on the effects that invasive cane toads, a toxic prey species, have had on freshwater crocodile populations in 7 waterholes of the Victoria River, Australia, before and up to 14 years after toads invaded. We recorded observations of crocodiles attacking toads, dissected dead crocodiles to determine if they had eaten toads and indexed the abundances of cane toads, live crocodiles and dead crocodiles. Following toad-invasion we observed crocodiles attacking cane toads. Dead crocodiles were only observed following the invasion of toads and 62% of the 71 dead crocodiles we dissected had toads in their stomachs. Counts of dead crocodiles showed a humped relationship with time since toad invasion and declined markedly after 3 years post-toad invasion. Live crocodile abundance declined sharply following toad-invasion, but this decline attenuated approximately 4 years post-invasion. The pulse of crocodile mortality and attenuation of the rate of crocodile population decline suggests that crocodiles have evolved or learned to enable co-existence with toads. However, crocodile populations have shown no sign of recovery in the 8–14 years post toad invasion. Our findings highlight that adaptation by native species to the presence of invaders may be imperfect and thus may not necessarily entail numerical recovery of populations to pre-invasion levels, but instead downward shifts to new equilibria due to ongoing interactions with invaders.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Daniel J. Ingram; Margi Prideaux; Nicola K. Hodgins; Heidrun Frisch-Nwakanma; Isabel C. Avila; Tim Collins; Mel Cosentino; Lucy W. Keith-Diagne; Helene Marsh; Matthew H. Shirley; Koen Van Waerebeek; Maximin K. Djondo; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, in some places has been sustained for millennia, and can be an important source of nutrition, income, and cultural identity to communities. Yet, economic opportunities to exploit wildlife at higher levels have led to unsustainable exploitation of some species. In the literature, there has been limited focus on the exploitation of aquatic non-fish animals for food and other purposes. Understanding the scope and potential threat of aquatic wild meat exploitation is an important first step toward appropriate inclusion on the international policy and conservation management agenda. Here, we conduct a review of the literature, and present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We find that consumption of aquatic megafauna is widespread in coastal regions, although to varying degrees, and that some species are likely to be at risk from overexploitation, particularly riverine megafauna. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

A trophic cascade initiated by an invasive vertebrate alters the structure of native reptile communities - Benjamin Feit; Tim Dempster; Tim S. Jessop; Jonathan K. Webb; Mike Letnic (Global Change Biology, 2020)
Invasive vertebrates are frequently reported to have catastrophic effects on the populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species then other species will indirectly benefit due to ecological release from interactions with directly impacted species. However, evidence that invasive vertebrates trigger such trophic cascades and alter community structure in terrestrial ecosystems remains rare. Here, we ask how the cane toad, a vertebrate invader that is toxic to many of Australia's vertebrate predators, influences lizard assemblages in a semi‐arid rangeland. In our study area, the density of cane toads is influenced by the availability of water accessible to toads. We compared an index of the abundance of sand goannas, a large predatory lizard that is susceptible to poisoning by cane toads and the abundances of four lizard families preyed upon by goannas (skinks, pygopods, agamid lizards and geckos) in areas where cane toads were common or rare. Consistent with the idea that suppression of sand goannas by cane toads initiates a trophic cascade, goanna activity was lower and small lizards were more abundant where toads were common. The hypothesis that suppression of sand goannas by cane toads triggers a trophic cascade was further supported by our findings that small terrestrial lizards that are frequently preyed upon by goannas were more affected by toad abundance than arboreal geckos, which are rarely consumed by goannas. Furthermore, the abundance of at least one genus of terrestrial skinks benefitted from allogenic ecosystem engineering by goannas where toads were rare. Overall, our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure and integrity of native communities extending beyond their often most obvious and frequently documented direct ecological effects.

Germination niches and seed persistence of tropical epiphytic orchids in an urban landscape - Muhammad Izuddin; Tim Wing Yam; Edward L. Webb (Journal of Plant Research, 2019)

Invasive cane toads might initiate cascades of direct and indirect effects in a terrestrial ecosystem - Benjamin Feit; Christopher E. Gordon; Jonathan K. Webb; Tim S. Jessop; Shawn W. Laffan; Tim Dempster; Mike Letnic (Biological Invasions, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Specific niche requirements drive long-term survival and growth of translocated epiphytic orchids in an urbanised tropical landscape - Muhammad Izuddin; Tim Wing Yam; Edward L. Webb (Urban Ecosystems, 2018)

A robust impact assessment that informs actionable climate change adaptation: future sunburn browning risk in apple - Leanne Webb; Rebecca Darbyshire; Tim Erwin; Ian Goodwin (International Journal of Biometeorology, 2017)

Causal modelling applied to the risk assessment of a wastewater discharge - Warren L. Paul; Pat A. Rokahr; Jeff M. Webb; Gavin N. Rees; Tim S. Clune (Environmental Monitoring and Assessment, 2016)

Mechanisms for the land/sea warming contrast exhibited by simulations of climate change - Manoj M. Joshi; Jonathan M. Gregory; Mark J. Webb; David M. H. Sexton; Tim C. Johns (Climate Dynamics, 2008)

Comparison of physical characteristics between created and natural estuarine marshes in Galveston Bay, Texas - Tim P. Delaney; James W. Webb; Thomas J. Minello (Wetlands Ecology and Management, 2000)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)